Repeated Dose 90-Day Oral Toxicity Study of Kushta-e-Faulad: A Traditional Unani Hematinic Agent - Husain, Gulam Mohammed; Kodavath, Divya; Ahmad, Tasleem; Munshi, Younis Iftikhar; Urooj, Mohd (International Journal of Pharmaceutical Investigation, 2026)
Background Kushta is an ultra-fine powdered product in Unani medicine, created through calcination of animal, metals and mineral substances. Kushta-e-Faulad is a traditional compound Unani formulation to manage Su’al-Qinya (anemia) and Du‘f al-Kabid (liver Dysfunction). Despite its traditional use, its safety profile has not yet validated through scientific studies. Objectives The current investigation was aimed to evaluate 90-day oral toxicity of Kushta-e-Faulad, an Unani prescribed formulation commonly employed as hematinic. Materials and Methods Kushta-e-Faulad safety was assessed in rats following OECD-408. The medication was given orally at 03 doses i.e. 6, 30, and 60 mg/kg bw-as an Aqueous suspension in 0.3% CMC. Animals were noticed for changes in body weight, feed consumption, toxicity signs, morbidity and mortality throughout the study. Hematology, clinical chemistry, level of electrolytes, gross pathology, comparative organ weight, and histological investigation were carried out at the conclusion of the study. Results Increase in body weight, feed consumption, and clinical indicators of systemic toxicity did not significantly change throughout treatment with the tested medication. Haematological parameters did not differ significantly from those of the control group. At the end of the research, a gross necropsy showed that neither the drug-treated group nor the control animals had changed. Hematological values were similar to controls, and gross necropsy showed no changes in any group. It was discovered that the relative organ weight of the drug-treated and control groups was similar. When comparing drug-treated animals to those in the control group, no noticeable histological alterations were seen. Control and treatment groups showed similar relative organ weights, with no alterations in histology of various organs. Conclusion The study confirmed that hematological and serum parameters remained unaffected, showing no significant changes in toxicity point of view. No significant difference observed in relative organ weight. Histological findings showed no significant changes. Therefore, based on findings Kushta-e-Faulad can be regarded as safe in rats at doses up to 60 mg/kg body weight.
Keywords: Hematinic; Kushta-e-Faulad; Unani; Traditional.